Sosialisasi Edukatif pada Lingkungan Sekolah Tentang Pencegahan Bullying terhadap Siswa Sekolah di SDN III Kronjo Kabupaten Tangerang Provinsi Banten - Irma Nurmala Dewi; Asep Sapaatullah; Ganjar Sidik Gandara; Dedy Khaerudin; Teddy Iman Fatullah; Abdul Gofar (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Following their primary education at home, children attend school where they learn to read, write, and count. Aside from that, school is a place where children can develop their minds and learn about morals and ethics. As a second learning environment after home, schools should provide students with opportunities to hone and gain knowledge for their future needs. However, the prevalence of bullying in the school environment scares some students. The method of this research uses an outreach campaign to educate elementary school students about bullying prevention. As a result of this service, bullying among elementary school students continues in the school environment. This hurts the behavior of children who are still young during their growth and development.